“Njagani Plesiran” Upaya Adaptasi Kenormalan Baru Di Klenteng Agung Sam Poo Kong Semarang - Akbar, Syahrul; Noviyanti, Evi; Khadijah, Ute Lies Siti; Suganda, Dadang (Jurnal Ilmiah Pariwisata, 2022)
As one of the largest industries in the world, tourism has become a rapidly growing phenomenon, yet this industry is very vulnerable to its surrounding issues, including the current Covid-19 pandemics. The travel restriction imposition has made Central Java government reconsider about its initial tourism development strategies as they need to minimise the spread of the virus while trying to accelerate the tourism sector. To implement this adjusted tourism strategies, based on policy analysis taken by the Central Java Provincial Government and its applications in the field, a tourism program named “Njagani Plesiran” was launched. This jargon “Njagani Plesiran” was derived from local Javanese language which literally means maintaining tourism activities. This study uses a literature study method in analysing the tourism policies. To ensure the effectiveness and efficiency of the implementation of the Njagani Plesiran, the Great Chinese Temple Sam Poo Kong promotes the programes through various media channels. The expected impact of this tourism program implementation is that while local mobility within the country is still allowed yet regulated, allowing tourism businesses to remain open, the spread of Covid-19 in tourist destinations can be controlled and eventually prevented. Keywords: Covid-19, Tourism Crisis, Klenteng Agung Sam Poo Kong, Njagani Plesiran , Public Policy